Relationship Between Level of Serum 25-Hydroxyvitamin D and Risk of Squamous Cell Carcinoma in an Iranian Population - Mahboobeh-Sadat Hosseini; Fereshteh Salarvand; Amir Houshang Ehsani; Pedram Noormohammadpour; Shadi Azizzadeh; Mohaddese Mousavi; Mona Morsali (Mattioli1885, 2019)
Background: The relationship between vitamin D and skin squamous cell carcinoma (SCC) is not well defined. Objective: To investigate the relationship between vitamin D levels and the incidence of skin SCC for the first time in Iran. Methods and Study Design: In this case-control study, 126 subjects were enrolled (63 in each group) out of referents to Razi Skin Hospital in Tehran in 2014. The risk factors for cancer gathered by self-reported questionnaires and blood samples were obtained to measure the level of 25-hydroxyvitamin D. Multivariate logistic regression was used to neutralize the effect of confounding factors. Results: Cases of SCC were more likely to be in men, older than 49 years and working in an outdoor environment, and with longtime exposure to sunlight and a personal history of skin cancers. Family history of skin cancer and of cigarette smoking were not significantly related to SCC. In the SCC and control groups, 69.8% and 31.7%, respectively, had sufficient levels of vitamin D (P < 0.001). Mean level of 25-hydroxyvitamin D was 40.99 ng/mL in the SCC group and 26.34 ng/mL in the control group (P < 0.05). In the unadjusted model, the level of vitamin D as a continuous variable was positively related to SCC risk. In the adjusted model, vitamin D did not independently predict the likelihood of SCC. Conclusion: Vitamin D level and SCC risk are directly related, although not in an independent fashion. Indeed, this relation is severely confounded by exposure to sunlight, which was evidenced by an increased vitamin D level in the people working outside and the higher prevalence of SCC in the same population.